Impaired β-arrestin recruitment and reduced desensitization by non-catechol agonists of the D1 dopamine receptor - David L. Gray (Nature Portfolio, 2018)
Dopamine receptor agonists are used for the treatment of various psychiatric diseases. Here, the authors screen approximately three million compounds and identify a novel class of D1R agonists that do not have a catechol scaffold and possess promising pharmacokinetic properties.